Core needle biopsy is an inferior tool for diagnosing cervical lymphoma compared to lymph node excision. (3rd July 2021) - Krarup Sigaard, Rasmus; Wennervaldt, Kasper; Munksgaard, Lars; Rahbek Gjerdrum, Lise Mette; Homøe, Preben
Abstract: Background: In Denmark, fine needle aspiration is the standardized tool for obtaining tissue samples from lymph nodes (LN) of the neck. However, because of a low specificity toward lymphomas, LNs suspicious for this disease are often surgically removed and examined. International studies have implied that a core needle biopsy (CNB) is sufficient for detecting lymphomas, thereby potentially avoiding surgery. However, all studies have been conducted retrospectively and the goal of this prospective study was to find the true sensitivity of CNB. Material and Methods: Fifty-seven patients were enrolled in the study, one was excluded due to lack of CNB material. LNs suspected for lymphoma were surgically removed from the neck, whereafter a CNB was obtained from the removed LN. The CNB and the remaining part of the LN were sent to the Department of Pathology for further processing and the samples were blinded and examined by two pathologists separately. A consensus diagnosis was reached in cases with divergent diagnostic proposals. Sensitivity of the CNB method in comparison to whole tissue sections for lymphoma diagnosis was calculated. Results: The CNB method gave the correct diagnosis in 66% of lymphoma cases, was inconclusive in 14% and gave an incorrect lymphoma subtype in 18%. In 2% the CNB wrongly resulted in a benign diagnosis. CNB was correct in all the non-lymphoma cases; thereby retaining a specificity of 100%. Conclusion: This prospective study found a sensitivity of 66% for diagnosing lymphoma with a CNB. As the CNB in this study was obtained under optimal conditions, unlike in clinical practice, we conclude that CNB cannot be recommended as a standard tool for diagnosing lymphomas.